Pencak Silat Wajah Budaya Bangsa Indonesia - Khairul Sasmita; Eri Barlian; Padli Padli (Departement of Mathematics Education, 2023)
Pencak Silat, is one of the forms of identity for the Indonesian archipelago martial art, contains education that develops in society. In the modern world, silat is not only a means of martial arts but has developed into an effort to maintain health through exercise. Silat also functions as a means of physical and spiritual education through a process of formal tiered education stages through regulations made by each silat school. Identity is part of the culture and social environment that can shift according to the dynamics of people's lives. Identity develops based on space and time for each generation in the world of everyday life which originates from human thoughts and actions and develops into real practice. Physical and spiritual education that is instilled through silat forms a strong, strong and virtuous national character and develops into a national identity character. According to the demands of the modern world, the role of martial arts is developing, apart from protecting oneself, it is also a means of maintaining health through sports so that physical and spiritual balance is a way to increase people's productivity.